2008
DOI: 10.3171/jns/2008/108/4/0649
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient brain tumor surgery: innovation in surgical neurooncology

Abstract: Object Recent studies of conventional craniotomies and image-guided biopsies have afforded a solid characterization of surgical morbidity and the timing of its occurrence. This report outlines a novel 11-year experience with outpatient image-guided biopsy and outpatient craniotomy for supratentorial intraaxial brain tumors. Methods During the period between August 1996 and May 2007, 117 awake image-guided biopsies and 145 elective craniotomies for tumor resection were prospectively selected to be performed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 34 publications
2
90
0
3
Order By: Relevance
“…8 As well, an awake craniotomy (AC) can be safely used for many supratentorial tumours, allowing for a potentially faster recovery and discharge from the hospital, as short stay or even as day surgery. [9][10][11][12] The purpose of this retrospective observational study was to assess the incidence of same-day discharge from hospital in patients undergoing craniotomy for supratentorial brain tumours as well as to explore the associated perioperative factors, anesthesia techniques, and complications.…”
Section: Résultats Les Données De 329 Patients (âGe Moyen [Et]mentioning
confidence: 99%
“…8 As well, an awake craniotomy (AC) can be safely used for many supratentorial tumours, allowing for a potentially faster recovery and discharge from the hospital, as short stay or even as day surgery. [9][10][11][12] The purpose of this retrospective observational study was to assess the incidence of same-day discharge from hospital in patients undergoing craniotomy for supratentorial brain tumours as well as to explore the associated perioperative factors, anesthesia techniques, and complications.…”
Section: Résultats Les Données De 329 Patients (âGe Moyen [Et]mentioning
confidence: 99%
“…12 Although numerous surgical specialties have adopted ERAS and Fast-track protocols for various ambulatory and inpatient surgeries, the literature attesting to their current use in an adapted form to neurosurgical cases is scarce. 3,4,6,10,33 A few studies have reported that outpatient brain tumor surgery, spinal decompression, and carotid endarterectomy are safe and feasible in selected patients. 3,4,6,10,33 A comprehensive assessment of the applicability of an ERAS-like perioperative protocol for neurosurgical procedures is lacking.…”
Section: Avenues For Future Improvementmentioning
confidence: 99%
“…Operative intervention does not provide ablasticity, therefore, the development and application of techniques with a selective effect on tumor cells including photodynamic therapy (PDT) is of current interest now. PDT increases a radicality degree in glioma removal due to the fact that tumor cells are destroyed by the mechanisms, which differ from the effect of chemotherapy or radiotherapy [4], improves long-term results increasing patients' survival [5]. PDT is considered [5][6][7] to be based on three main mechanisms of action.…”
mentioning
confidence: 99%
“…PDT increases a radicality degree in glioma removal due to the fact that tumor cells are destroyed by the mechanisms, which differ from the effect of chemotherapy or radiotherapy [4], improves long-term results increasing patients' survival [5]. PDT is considered [5][6][7] to be based on three main mechanisms of action. Firstly, the interaction between light energy (photons) and a photosensitizer selectively accumulated in tumor cells results in the occurrence of free radical compounds, which damage mitochondria, DNA and membranes of tumor cells causing their apoptosis and lysis.…”
mentioning
confidence: 99%